«GREEN» RESTORATION OF THE STEEL INDUSTRY OF UKRAINE - Логвиненко, Євгеній (SWorldJournal, 2025)
The article addresses current issues regarding the restoration of Ukraine’s steel industry in the context of post-war reconstruction, considering environmental factors. An analysis of the current state of steel production in Ukraine was conducted, particu